2007
DOI: 10.7150/ijms.4.159
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of vibration exercise for glycemic control in type 2 diabetes patients

Abstract: Although it is well documented that persons suffering from diabetes type 2 profit from muscular activities, just a negligible amount of patients take advantage of physical exercises. During the last decade, vibration exercise (VE) could be established as an effective measure to prevent muscular atrophy and osteoporosis with low expenditure of overall exercise-time. Unfortunately, little is known about the metabolic effects of VE. In the present study we compared VE with the influence of strength training and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 23 publications
7
57
1
6
Order By: Relevance
“…Baum et al (2) revealed FBS and HbA1c levels in type II diabetics were reduced by approximately 6.3% and 0.3% respectively after 12 weeks of WBV using a horizontal swinging platform (30-35 Hz, 2 mm amplitude, 8 bouts of 30 seconds, 3 days a week). More recently, del Pozo-Cruz et al (9) reported 12 weeks of WBV training (12)(13)(14)(15)(16) Hz, 4 mm, 3 days a week) significantly improved levels of FBS and HbA1c.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baum et al (2) revealed FBS and HbA1c levels in type II diabetics were reduced by approximately 6.3% and 0.3% respectively after 12 weeks of WBV using a horizontal swinging platform (30-35 Hz, 2 mm amplitude, 8 bouts of 30 seconds, 3 days a week). More recently, del Pozo-Cruz et al (9) reported 12 weeks of WBV training (12)(13)(14)(15)(16) Hz, 4 mm, 3 days a week) significantly improved levels of FBS and HbA1c.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration training has been suggested to be a useful alternative or supplement to current exercise prescriptions for diabetic patients (2). It is thought that vibration training stimulates muscle contraction, increases peripheral blood flow, and energy consumption (3,4), all of which may help with diabetes and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…First, a regularly performed training increases the content of the glucose transporter protein GLUT-4 within the cells. Secondly, a single bout of muscle contractions leads to a translocation of GLUT-4 to the sarcolemmal membrane which acutely enhances glucose transport capacity [16].…”
Section: Discussionmentioning
confidence: 99%
“…De este modo, incrementos en los depósitos de glucógeno muscular, debido al aumento de los niveles de masa muscular (84), en combinación con mejoras de las células β-pancreáticas (75) y las vías de seña-lización de la glucosa y su acción en el músculo esquelético (85), explica las mejoras en el control glucémico medido a través de la reducción en los niveles de Hb1Ac (77,79,(86)(87)(88), la reducción en los niveles de glucosa en sangre (88), insulina (75) y la respuesta de la insulina a un test de tolerancia a la glucosa (89).…”
Section: Entrenamiento Contra Resistencias Y Diabetes Mellitusunclassified
“…En términos de salud, no menos importantes son las adaptaciones positivas como respuesta al RT sobre mejoras en la autopercepción de salud (82), así como en la reducción en la ingesta de fármacos (77,87).…”
Section: Entrenamiento Contra Resistencias Y Diabetes Mellitusunclassified